Software development for optimal design of different precast slabs - Noorzaie, Jamaloddin; Wong, J. N.; Thanoon, Waleed Abdulmalik; Jaafar, Mohd. Saleh (Universiti Putra Malaysia Press, 2009)
Precast concrete technology forms an important part in the drive towards a full implementation of the Industrialized Building System (IBS). The IBS requires building components and their dimensions to be standardized, and preferably cast off site. Slabs are major structural elements in buildings, other than beams and columns. Standardized and optimized slabs can significantly enhance the building industries in achieving the full implementation of the IBS. Nevertheless, this requires computer techniques to achieve standardized and optimized slabs which can satisfy all building design requirements, including the standards of architectural and structural design standards. This study proposed a computer technique which analysed and designed five different types of slabs which will satisfy all the requirements in design. The most commonly used slabs included in this study were the solid one way, solid two way, ribbed, voided and composite slabs. The computer techniques enable the design of the most optimized sections for any of the slab types under any loading and span conditions. The computer technique also provides details for the reinforcements required for the slabs.